1991
DOI: 10.1149/1.2085587
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Air Cathodes Containing Ion Conductive Oxides

Abstract: This study is an attempt to improve the performance of Pt/ZrO2 high-temperature air cathodes by imitating porous electrodes of liquid electrolyte fuel cells. Ion conductive oxides were introduced into platinum electrodes in expectation of playing the same electrochemical role as the liquid electrolyte penetrating the porous electrodes. The oxide-mixed platinum electrodes prepared were modeled on a pore whose inner wall was covered with a gas permeable electrolyte film. An analysis based on the pore model predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 18 publications
10
98
0
Order By: Relevance
“…These observations are at ary (TPB) at the surface of the electrocatalyst/dense variance with the predictions of the model by Kenjo electrolyte membrane (e.g. LSM and the dense YSZ et al [7]. However, their results are entirely conmembrane) contributes to the charge transfer resistent with the model presented by Tanner et al action; hence the presence of V, in the denominator…”
supporting
confidence: 72%
See 1 more Smart Citation
“…These observations are at ary (TPB) at the surface of the electrocatalyst/dense variance with the predictions of the model by Kenjo electrolyte membrane (e.g. LSM and the dense YSZ et al [7]. However, their results are entirely conmembrane) contributes to the charge transfer resistent with the model presented by Tanner et al action; hence the presence of V, in the denominator…”
supporting
confidence: 72%
“…With a 10 pxm thick YSZ film as the electrolyte, the The role of composite electrodes, comprising a area specific resistance of the electrolyte is only mixture of a solid electrolyte and an electronic about 0.05 fjcm 2 at 800N C thus making an efficient conductor, or a mixed ionic-electronically conductoperation of an SOFC at such a low temperature in ing (MIEC) material, on electrode kinetics has been principle possible. However, it is usually observed examined by a number of researchers [7][8][9][10][11]. The that despite a low ohmic contribution, the area rationale for the use of a composite or an MIEC electrode is that it allows a spreading of the reaction RT zone from the electrolyte/electrode interface into the act -zF i = R,,i (2) electrode.…”
mentioning
confidence: 99%
“…Note that there are no terms containing I e in Eq. (37). However, it is important to note that I e is not zero, although usually |I e | |I i | in the present case of fuel cells.…”
Section: A Solid Oxide Fuel Cellmentioning
confidence: 86%
“…Recent work has shown that cathodic polarization can be substantially reduced provided the porous cathode is mixed conducting [37][38][39][40]. For this reason, the cathode must either be made of a single-phase MIEC material, or a composite mixture of an oxygen ion conductor (e.g.…”
Section: Application Of Space Charge Model In Composite Cathodementioning
confidence: 99%
“…Effort was directed in three areas: (1) Further development of the model on the role of connectivity on ionic conductivity of porous bodies, including the role of grain boundaries and space charge region. (2) Calculation of the effect of space charge and morphology of porous bodies on the effective charge transfer resistance of porous composite cathodes.…”
Section: Introductionmentioning
confidence: 99%